2017
DOI: 10.1080/17434440.2017.1343142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NinePoint Medical’s Nvision VLE device for gastrointestinal applications

Abstract: The incidence of esophageal adenocarcinoma (EAC) has increased over the last few decades. With a known precursor lesion, Barrett's esophagus, this remains a target for screening and surveillance with the goal of detecting and providing curative treatment for early neoplasia. Areas covered: Current surveillance techniques rely on white light endoscopy and random tissue sampling which is time consuming, costly and prone to sampling error. Volumetric laser endomicroscopy (VLE), a second-generation optical coheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…VLE, compared to the original OCT system can scan a wider area (6 cm circumferential segment) of the esophagus in real time, to create high resolution (7 um), 3D cross-sectional images while reaching a depth of 3 mm below the mucosa [28]. The Nvision VLE offers a volumetric view of approximately 10.000 mm 2 and has a significantly improved imaging speed and resolution (25 times higher than endoscopic ultrasound) as compared to the first-generation OCT systems [29]. The cross-sectional view of the Nvision VLE can collect approximately 1200 cross-sectional images across the targeted 6 cm, with an option to zoom in for closer examination [29].…”
Section: Barrett's Esophagus (Be)mentioning
confidence: 99%
See 3 more Smart Citations
“…VLE, compared to the original OCT system can scan a wider area (6 cm circumferential segment) of the esophagus in real time, to create high resolution (7 um), 3D cross-sectional images while reaching a depth of 3 mm below the mucosa [28]. The Nvision VLE offers a volumetric view of approximately 10.000 mm 2 and has a significantly improved imaging speed and resolution (25 times higher than endoscopic ultrasound) as compared to the first-generation OCT systems [29]. The cross-sectional view of the Nvision VLE can collect approximately 1200 cross-sectional images across the targeted 6 cm, with an option to zoom in for closer examination [29].…”
Section: Barrett's Esophagus (Be)mentioning
confidence: 99%
“…The Nvision VLE offers a volumetric view of approximately 10.000 mm 2 and has a significantly improved imaging speed and resolution (25 times higher than endoscopic ultrasound) as compared to the first-generation OCT systems [29]. The cross-sectional view of the Nvision VLE can collect approximately 1200 cross-sectional images across the targeted 6 cm, with an option to zoom in for closer examination [29].…”
Section: Barrett's Esophagus (Be)mentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is similar to EUS in principle but uses lowintensity infrared light (at a wavelength ranging 750–1300 nm) instead of sound, thus allowing for significantly higher resolution images. 116,117 With OCT, visualization of layer architecture (and structures such as blood vessels, lymphoid aggregates, crypts, submucosal glands) is possible at a level of detail approaching that of histopathology. 118-120 Although large studies comparing the accuracy of OCT to other endoscopic modalities are lacking, several small studies have shown that OCT can distinguish benign from malignant lesions with superior accuracy to that of brush cytology.…”
Section: Initial Evaluation and Surveillance Of Dominant Stricturesmentioning
confidence: 99%